Exiles and expatriates in the history of knowledge, 1500-2000 - Burke, Peter 1937- (The Menahem Stern Jerusalem lectures, 2017)
The view from the edge -- A global topic -- Early modern exiles -- Three types of expatriate -- The great exodus -- Appendix: One hundred female refugee scholars in the humanities, 1933-1941